Carboxyl-terminal deletion and point mutations decrease the transforming potential of the activated rat neu oncogene product. - Mikami, Y (1992)
The rat neu oncogene encodes a constitutively activated growth factor receptor/transmembrane tyrosine kinase, p185Tneu, that is structurally similar to yet distinct from the epidermal growth factor receptor. To explore the role of the carboxyl-terminal region and of putative autophosphorylation sites in regulating the activity of the rat p185Tneu (T, transforming) protein, we used site-directed mutagenesis to generate a p185Tneu mutant in which a putative tyrosine autophosphorylation site (residue 1253) at the extreme carboxyl terminus was replaced by a phenylalanine residue and a mutant in which the carboxyl-terminal 122 amino acids were deleted. These proteins were expressed in NIH 3T3 cells at comparable levels and exhibited similar autophosphorylation activity, exogenous substrate phosphorylation ability, oligomerization levels, and responsiveness to a partially purified neu-activating factor. However, the mutant p185Tneu proteins displayed a decreased transforming capacity both in vitro and in vivo. This analysis demonstrated that the carboxyl-terminal domain and at least one putative tyrosine autophosphorylation site of p185Tneu play a role in positively regulating the cell growth-regulating properties of the neu protein.